Challenges of Undergraduate Female Married Students at the University of Albutana - Susan Zroog; Fatima Elhag Ahmed; Safaa Rashad; Abdelhakam Ali (AlQalam Journal of Medical and Applied Sciences, 2025)
Undergraduate women face significant challenges in pursuing higher education. Married female students in particular demonstrate lower enrollment rates, as they struggle to balance domestic responsibilities with academic aspirations, making degree completion particularly challenging. This descriptive cross-sectional study examined the challenges faced by married female undergraduate students in medical colleges, the University of Albutana. Data were collected through an online survey questionnaire (Google Form) designed by the authors and distributed via WhatsApp and Facebook. The study included 60 respondents. Data were analyzed using SPSS. Descriptive statistics (means, frequencies, standard deviations, and percentages) summarized the dataset, while correlation analysis examined relationships between variables. One-way ANOVA statistical test was also used. Results indicate significant challenges, with high mean scores in areas such as lack of study time (M=3.59), financial and emotional support from spouses (M=3.74), and difficulties balancing household and academic duties (M=3.44). Strong correlations were found between marital status and academic struggles (p<0.001), highlighting the dual burden these students endure. The findings underscore the need for institutional support systems to alleviate these pressures and improve academic outcomes for married female students. Married female students face multiple distinct challenges during their university studies. The results demonstrate the need for targeted support mechanisms to address these difficulties. Inclusive university policies—including flexible scheduling, financial aid, and family support—can help married female students overcome challenges, ensuring equal access to education and higher retention rates.